DETERMINASI BUDAYA TRI HITA KARANA DAN PENGETAH UAN AKUNTANSI TERHADAP KINERJA USAHA MIKRO, KECIL DAN MENENGAH DI KOTA DENPASAR - I Gusti Ngurah Putra Harthawan; I Gd Ari Sudira; I Komang Arnata (KRISNA: Kumpulan Riset Akuntansi, 2025)
Micro, small and medium enterprises have an important role in increasing economic growth in a region.Micro, small and medium enterprises are one of the potential tax contributors. Research on micro, smalland medium enterprises is very necessary to spur the growth of this business group so that the regionaleconomy continues to move positively. This study aims to determine the influence of Tri Hita Karana(THK) culture and accounting knowledge on the performance of micro, small and medium enterprises inDenpasar City. The number of respondents involved in the study was 100 micro, small and mediumenterprise managers. The results of the regression test showed that if the THK culture improves, theperformance of micro, small and medium enterprises will increase. The results of the study also showedthat accounting knowledge significantly drives the increase in the performance of micro, small andmedium enterprises.